The genomic landscape of esophageal squamous cell carcinoma cell lines - Chao Zhang; Chenghao Li; Jian Zhong Su; Kuaile Zhao; Longlong Shao; Jiaying Deng (Cancer Cell International)
Abstract Background Research on the genomic characteristics of common esophageal squamous cell carcinoma (ESCC) cell lines, including exome mutations and mRNA expression, is limited. This study aims to elucidate the malignancy, invasion capability, classical cancer-related signaling pathways, and immune status of ESCC cell lines, providing a detailed genomic landscape and highlighting the unique features of each cell line. Methods Whole exome and RNA sequencing were conducted on ESCC cell lines TE-1, ECA-109, KYSE-30, KYSE-150, KYSE-180, KYSE-450, and KYSE-510, with the normal epithelium cell line Het-1a as a comparison. Bioinformatics methods analyzed gene mutation types, mutation frequencies, RNA expression, and classical cancer-related signaling pathways. Specific analyses were also performed on tumor burden, genes related to differentiation, invasion, immunity, and gene enrichment in each cell line. Results The highest tumor mutation burden (TMB) was 70.4 mutations per megabase (mut/MB) in KYSE-150, while the lowest was 48.7 mut/MB in KYSE-510. Mutations in the Hippo, Notch, PI3K, RTK-Ras, and Wnt signaling pathways were present in all cancer cell lines. Mutations were significantly enriched in signature 3, associated with defective homologous recombination deficiency (HRD). The NRF2 signaling pathway exhibited mutations in KYSE-180, KYSE-450, and TE-1 cell lines. The cell cycle gene mutation frequency was low, occurring only in KYSE-30 and TE-1 cell lines. The expression profiles of KYSE-510 and ECA-109 were similar. The KYSE-150 cell line showed up-regulated invasion genes, while the KYSE-450 cell line had significantly down-regulated poor differentiation-related genes. Immune-related genes were up-regulated in the ECA-109 cell line. Conclusion The molecular profiles generated in this study provide detailed information on gene mutations and expression in common ESCC cell lines. The KYSE-150 cell line exhibited a prominent invasion capability, while the ECA-109 cell line showed up-regulated immune properties. This genomic landscape offers valuable insights for future research and therapeutic strategies in ESCC.